Phytochemical Screening, In vitro Antioxidant and Enzyme Inhibitory Properties, and Acute Toxicity of Extracts from the Aerial Parts of Ephedra nebrodensis, a Source of Bioactive Compounds - Hamoudi, Meriem; Amroun, Djouher; Boutefnouchet, Sabrina; Bensouici, Chawki; Kaoula, Samira; Harzallah, Daoud; Khennouf, Seddik; Dahamna, Saliha (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Due to the strong association between the chemistry of medicinal plants and their biological properties, it is important to determine their phytochemical composition to justify experimental tests. Objective: The aim of this study was to evaluate the in vitro antioxidant and the enzyme inhibitory properties and to identify the bioactive compounds present in the extracts of Ephedra nebrodensis growing in Algeria. Methods: Total phenolic and flavonoids content in these extracts were quantified by Folin- Ciocalteu and aluminum chloride methods. The antioxidant capacity was assessed using DPPH, ABTS, β-carotene/linoleic acid, CUPRAC and FRAP assays, and in vitro cholinesterase activity against acetylcholinesterase and butyrylcholinesterase were evaluated. The chemical constituents of the extracts were analyzed by high-performance liquid chromatography coupled with mass spectrometric detection and gas chromatography. For the acute toxicity study, extracts were administered to mice at single dose of 2 g/kg and 5 g/kg by gavage. Results: Plant extracts were rich in phenolic compounds. Ethyl acetate extract presented the highest phenolic (238.44 ± 1.50 μg GAE /mg of extract) and flavonoid (21.12 ± 0.00 μg QE /mg of extract) contents. Likewise, ethyl acetate extract showed potent radical scavenging and reducing properties. Ethanol-acetone extract showed inhibitory activity against acetylcholinesterase, and was a potent inhibitor of butyrylcholinesterase. In all extracts, flavonoids were the most abundant compounds. The phytochemical investigation showed the presence of alkaloids (ephedrine and pseudo-ephedrine). In the acute toxicity, the LD50 was superior to 5 g/kg body weight. There were no alterations in the histology of the liver and kidneys. Conclusion: This study demonstrated a good antioxidant potential and anticholinesterase activity of aerial parts of E. nebrodensis.
Keywords: Ephedra nebrodensis